4(2x-10)=-10(x-5)

Simple and best practice solution for 4(2x-10)=-10(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-10)=-10(x-5) equation:


Simplifying
4(2x + -10) = -10(x + -5)

Reorder the terms:
4(-10 + 2x) = -10(x + -5)
(-10 * 4 + 2x * 4) = -10(x + -5)
(-40 + 8x) = -10(x + -5)

Reorder the terms:
-40 + 8x = -10(-5 + x)
-40 + 8x = (-5 * -10 + x * -10)
-40 + 8x = (50 + -10x)

Solving
-40 + 8x = 50 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-40 + 8x + 10x = 50 + -10x + 10x

Combine like terms: 8x + 10x = 18x
-40 + 18x = 50 + -10x + 10x

Combine like terms: -10x + 10x = 0
-40 + 18x = 50 + 0
-40 + 18x = 50

Add '40' to each side of the equation.
-40 + 40 + 18x = 50 + 40

Combine like terms: -40 + 40 = 0
0 + 18x = 50 + 40
18x = 50 + 40

Combine like terms: 50 + 40 = 90
18x = 90

Divide each side by '18'.
x = 5

Simplifying
x = 5

See similar equations:

| 3x+243=12x-9 | | 2x^4+18x^2-243=0 | | 218-2x=43x+23 | | Y=2x^2-16x+25 | | 17+2b-4c=4(a-7)-3 | | 192-6x=6x+12 | | y*12=-60 | | 7x+5-5x-2=11 | | 5a=0 | | 2x+2y+3z=3 | | 5y=13 | | -2x-5=x+7 | | -2w=-0,5 | | 4n^2-3n-13=0 | | 22(-c)=-66 | | 12-5x=2x^2 | | 33-16=8-16+5a+5 | | 12*5= | | (2x+1)(3x-8)=(5x-24)(2x-5)-192 | | 28-4a=6(2a-2)+24 | | 5x+1=2x+22 | | 0.80x-0.40(60+x)=-0.20(60) | | -5u-(-4)= | | x*2=7x | | 7(a-4)-2a=19+3(a+3) | | 0.04y+0.12(200-y)=0.34y | | 0.2(x+1)=10 | | 5x^2+1=0 | | 0.09y+0.09(900-y)=0.50y | | 1.2x-3.3=0.6x-2.58 | | 6x-16=2x+16 | | 5-8n+3n=10-85 |

Equations solver categories